2011
DOI: 10.3390/toxins3030309
|View full text |Cite
|
Sign up to set email alerts
|

Brown Spider (Loxosceles genus) Venom Toxins: Tools for Biological Purposes

Abstract: Venomous animals use their venoms as tools for defense or predation. These venoms are complex mixtures, mainly enriched of proteic toxins or peptides with several, and different, biological activities. In general, spider venom is rich in biologically active molecules that are useful in experimental protocols for pharmacology, biochemistry, cell biology and immunology, as well as putative tools for biotechnology and industries. Spider venoms have recently garnered much attention from several research groups wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 217 publications
(376 reference statements)
2
81
0
1
Order By: Relevance
“…Recently, it has shown that a meprin inhibitor suppresses the formation of atherosclerotic plaques ). The recombinant astacins could also be used as reagents for laboratorial tests to diagnose Loxoscelism, anti-loxosceles serum production, and in the treatment of envenomation (Chaim et al 2011). …”
Section: Spidermentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has shown that a meprin inhibitor suppresses the formation of atherosclerotic plaques ). The recombinant astacins could also be used as reagents for laboratorial tests to diagnose Loxoscelism, anti-loxosceles serum production, and in the treatment of envenomation (Chaim et al 2011). …”
Section: Spidermentioning
confidence: 99%
“…The possible therapeutic use of astacins from L. intermedia is the vascular diseases (acute myocardial infarction, acute ischemic stroke, thrombosed aortic aneurysms, pulmonary embolism, etc.) and as thrombolytic agents (Chaim et al 2011). Meprins, which are members of the astacin family, hydrolyze and inactivate several endogenous vasoactive peptides.…”
Section: Spidermentioning
confidence: 99%
See 1 more Smart Citation
“…L. intermedia venom is liquid, colorless, crystalline and extremely rich in proteases, alkaline phosphatase, hyaluronidases, phospholipases, metalloproteases among other components (Barbaro et al, 2005;Chaim et al, 2011;da Silveira et al, 2007a;da Silveira et al, 2007b;Tambourgi et al, 2000). The spread of the venom and consequent dermonecrosis observed in humans and rabbits are attributed to hyaluronidase (Futrell, 1992) and phospholipase D (also referred as sphingomyelinase D) activities (Appel et al, 2008;Kalapothakis et al, 2007;Tambourgi et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Their biological properties and proteinaceous nature render them useful in biological pest management as previously suggested (1)(2)(3)(4)(5). The venom of poisonous predators has novel peptides that have been isolated from snakes, scorpions, marine cone snails, spider and other animals including predatory insects.…”
Section: Introductionmentioning
confidence: 99%